Dynamic reductions for the nonlinear soil-foundation-structure system interactions = Dynamiczne redukcje dla nieliniowego modelowania interakcje systemu grunt-fundament-konstrukcja - Sakharov, Volodymyr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents new dynamic superelements for DOF (degrees of freedom) reduction. Proposed spectral superelements (SES) are based on the method of normal coordinates. The developed superelements with basis nodes (SEB) for the inhomogeneous systems are also shown.
Keywords: Finite Element Method (FEM); spectral superelement; diagonal matrix; SES; SEB; explicit method; VESNA-DYN; high-rise buildings; nonlinear analysis; metoda elementów skończonych (MES); superelementy spektralne; macierz diagonalna; metoda jawna; budynek wysokościowy; analiza nieliniowa